A quantitative study of virtual energy storage for rural heat pump heating system based on vehicle-to-home technology - Xinjia Gao; Ran Li; Siqi Chen; Yalun Li (Next Energy)
The advent of novel power systems, predominantly reliant on renewable energy sources such as wind and photovoltaics, has precipitated a surge in demand for energy storage solutions. Buildings are undergoing a metamorphosis, emerging as pivotal actors in the realm of electricity generation and consumption, with vast untapped potential for energy storage. However, current research is marred by a dearth of quantitative methodologies for assessing the existing virtual energy storage (VES) resources within building contexts. As a result, it is challenging to provide an accurate evaluation of their potential value and components. In this study, an equivalent battery model is employed, comprising parameters such as equivalent charging and discharging power and energy storage capacity. Integration of VES into traditional energy storage(TES) frameworks. The potential and composition of VES resources within the building area is analyzed. Then, the VES potential of vehicle-to-home system and heat pumps and building thermal capacity are analyzed for winter electric heating in Beijing. The results show that VES system is capable of delivering a maximum equivalent charging power of 432.816 kW, a maximum equivalent discharging power of 385.376 kW, and an equivalent energy storage capacity of 2165.64 kWh. VES can effectively participate in energy management in rural electric heating through rational design and scheduling. No configuration of TES is required. The objective of this work energy planning in the building sector is to provide practical quantitative tools and strategies. It provides guidance on the design and optimization of future distributed energy systems.